GROWTH AND YIELD OF CHICKPEA (CICER ARIETINUM L.) AS INFLUENCED BY GRADED LEVELS OF FERTILIZERS AND BIOFERTILIZERS - DINESH KUMAR; L. K. ARVADIYA; K. L. DESAI; , V. P. USADADIYA; A. M. PATEL (The Bioscan, 2015)
An experiment with three levels of fertilizers (100, 75 and 50% of RDF) and 4 levels of bio-fertilizers (B1: Control B2: Rhizobium as seed treatment + PSB as soil application, B3: Rhizobium as seed treatment + VAM as soil application, B4: Rhizobium and PSB both as seed treatment) was conducted to study the response of chickpea (Cicer arietinum L.). 100% RDF recorded significantly highest plant height (42.33 cm), no. of branches plant-1 (12.68), no. of nodules plant-1 (31.10), dry matter accumulation plant-1(18.05 g), no. of pods plant-1(44.19), seed yield (1854 kg ha-1) and stover yield (2722 kg ha-1) over 75 and 50% RDF. Among bio-fertilizers, treatment B4 recorded significantly higher plant height (42.11 cm), no. of nodules plant-1 (30.16), no. of pods plant-1 (44.01), seed yield (1824 kg ha-1) and stover yield (2709 kg ha-1) over control but found at par with B3 and B2. With respect to interaction effect it is interesting to note that the yield recorded with 75% RDF + B4 found as good as the yield obtained with 100% RDF + B4 indicates 25% saving of fertilizers. The use of bio-fertilizers with reduced quantity of chemical fertilizers is therefore recommended for better yield of chickpea.